The Effect of Fermentation Time on Protein and Fat Content in The Red Beans (Phaseolus Vulgaris L.) Tempeh - Nur Wulan; Sugeng Maryanto; Indri Mulyasari (UNIVERSITAS NGUDI WALUYO, 2021)
Red beans is one of the local foods that is included in the type of legume and has a high nutrition content of vegetable protein and low fat. Red beans can be processed into red beans tempeh, with a fermentation time treatment that can affect protein and fat levels. This research aims to describes the protein and fat content in fermented red beans tempeh for 3 days. This study uses Experimental Design research using a one-shot case study design, which is to provide treatment time of red beans tempeh for 3 days, each 3 pieces of tempeh / day with each treatment using 100 grams of red beans mixed with 0.1 gram of yeast tempeh Rhizopus sp. Tempeh that has been formed will be analyzed for the nutritional content of protein and fat.The result showed that the protein content in red beans tempeh on day 2 contained as much protein (13.64 grams), on day 3 (13.64 grams) and on day 4 (9.64 grams). While the fat content in red beans tempeh on day 2 is (0.62 grams), day 3 (1.11 grams) and day 4 (1.14 grams). The protein and fat content in red beans tempeh, the longer the fermentation, the more it will affect the nutrients.